The Spectacular Past : Popular History and the Novel in Nineteenth-Century France - Samuels, Maurice (Book collections on Project MUSE., 2004)
Samuels shows how new technologies allowed a cult of the spectacle to pervade the national consciousness of post-Revolutionary France, & argues that the realist fiction of Balzac & Stendhal was a reaction to the spectacular mode of historical representation.